Resiliencia académica, rendimiento académico y factores protectores en estudiantes de nivel socioeconómico bajo: revisión sistemática - Jimenez Cieza, Maria Fe (2023)
Academic resilience refers to the high probability of educational success despite vulnerabilities and adversities, in which there are different protective factors at play that may help achieve it. The present study aimed to review the empirical evidence of studies related to academic resilience and academic performance, and the protective factors present in students of low socioeconomic status. A research was carried out following the recommendations of the PRISMA guideline (Page et al., 2021) in Scopus, Scielo and Ebsco databases. Twelve articles that met the inclusion and exclusion criteria determined for this study were analyzed. The methodology used in most of the studies was an analysis of secondary databases. The results evidenced the positive relationship between resilience and academic performance. Likewise, it was found that protective factors (peer relationships, teacher-student and family support) vary in their role and impact on resilience and academic achievement or performance depending on each sociocultural context.